The results of endoscopic mucosal resection by dissection in the submucosal layer in treatment of early gastric cancer - M. V. Armasheva; V. N. Klimenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Based on the conducted research (60 patients) and analysis of the literature of this topic, it is possible to conclude that endoscopic mucosal resection with submucosal dissection for early gastric cancer is a highly effective and safe method of radical organsaving treatment with high quality of life in the future, which allows to recommend this treatment for this pathology.